Association between prior vaginal birth after cesarean and subsequent labor outcome. (18th April 2018) - Krispin, Eyal; Hiersch, Liran; Wilk Goldsher, Yulia; Wiznitzer, Arnon; Yogev, Yariv; Ashwal, Eran
Abstract: Objective: To estimate the effect of prior successful vaginal birth after cesarean (VBAC) on the rate of uterine rupture and delivery outcome in women undergoing labor after cesarean. Methods: A retrospective cohort study of all women attempting labor after cesarean delivery in a university-affiliated tertiary-hospital (2007–2014) was conducted. Study group included women attempting vaginal delivery with a history of cesarean delivery and at least one prior VBAC. Control group included women attempting first vaginal delivery following cesarean delivery. Primary outcome was defined as the rate of uterine rupture. Secondary outcomes were delivery and maternal outcomes. Results: Of 62, 463 deliveries during the study period, 3256 met inclusion criteria. One thousand two hundred and eleven women had VBAC prior to the index labor and 2045 underwent their first labor after cesarean. Women in the study group had a significantly lower rate of uterine rupture 9 (0.7%) in respect to control 33 (1.6%), p  = .036, and had a higher rate of successful vaginal birth (96 vs. 84.9%, p  < .001). In multivariate analysis, previous VBAC was associated with decreased risk of uterine rupture (OR = 0.46, 95% CI 0.21–0.97, p  = .04). Conclusions: In women attempting labor after cesarean, prior VBAC appears to be associated with lower rate of uterine rupture and higher rate of successful vaginal birth.